2017
DOI: 10.48550/arxiv.1702.03173
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Fragmentation process, pruning poset for rooted forests, and Möbius inversion

Abstract: We consider a discrete-time Markov chain, called fragmentation process, that describes a specific way of successively removing objects from a linear arrangement. The process arises in population genetics and describes the ancestry of the genetic material of individuals in a population experiencing recombination. We aim at the law of the process over time. To this end, we investigate sets of realisations of this process that agree with respect to a specific order of events and represent each such set by a roote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…It can be observed that the structure of the formulae of P(F t (T I )) is reminiscent of an inclusion-exclusion. This is to be expected, as it has been studied and proven [6] to be the case for single-crossover. It remains an open problem to give the same interpretation in the general partition framework we have developed.…”
Section: Now Use the Identitymentioning
confidence: 67%
See 2 more Smart Citations
“…It can be observed that the structure of the formulae of P(F t (T I )) is reminiscent of an inclusion-exclusion. This is to be expected, as it has been studied and proven [6] to be the case for single-crossover. It remains an open problem to give the same interpretation in the general partition framework we have developed.…”
Section: Now Use the Identitymentioning
confidence: 67%
“…Our objective is to obtain a formula for the law of the fragmentation process, that is, to be able to compute P(X t = δ) for any δ ∈ Y * (G ρ ). In [6] a formula is obtained on the single-crossover case, that is when G ρ only contains partitions of the type {{1, .., .m}, {m + 1, ..., n} : 1 < m < n}. In this case the main idea is to code the embedded jump chain of the fragmentation process by taking advantage of the fact that once the sites split they become independent.…”
Section: Fragmentation Treesmentioning
confidence: 99%
See 1 more Smart Citation